Sternberg Thinking Skills among Upper Secondary Vocational Students in STEM Subjects - Mahmud, Murni Farahin; Yee, Mei Heong; Md Arsad, Nur Nadia; Sukardi,; Wan Rojas , Wan Nur Ilyana Najihah (Journal of Technical Education and Training, 2025)
The development of 21st-century skills is critical for Vocational Education to meet Industrial Revolution 4.0 demands. This study addresses the gap arising from underperformance in creative thinking and declining achievement in Upper Secondary Vocational Programme (PVMA) STEM elective subjects. Rooted in Sternberg's Triarchic Theory, this research aims to identify the level of analytical, creative, and practical thinking skills among PVMA STEM students and analyze differences based on gender, STEM subjects, and socioeconomic status (SES). A quantitative research design was employed, utilizing a survey instrument adapted from Yee et al. (2022). The sample consisted of 158 PVMA students randomly selected from secondary schools in Batu Pahat, Johor. This study employed descriptive and inferential analyses to examine the research data. A significant difference was found in practical thinking skills based on gender (p=0.01). No significant differences were observed between gender in analytical or creative thinking. Furthermore, there was a significant difference in thinking skills based on STEM subjects (Analytical p=0.01, Creative p=0.02, Practical p=0.001). Conversely, no significant differences were found in analytical, creative, or practical thinking skills based on students’ socioeconomic status (p>0.05). In conclusion, the findings highlight the influence of gender and specific STEM subjects on thinking skills. Although socioeconomic status did not yield significant differences, the study supports that experiential and contextual learning approaches can help bridge socioeconomic gaps. These results provide valuable insights for educators and policymakers, emphasizing differentiated teaching strategies and promoting the development of equitable thinking skills among TVET students.